New insights into place of death for people with Alzheimer's disease, dementia and senility. Issue 1 (1st June 2011) - Verne, J; Harris, S; Ho, D
Abstract : Between 2001 and 2009, 15% of all deaths in England had a mention (ie, either an underlying or contributory mortality coding) of Alzheimer's disease, dementia or senility. Over this period there was a 57% increase in the number of mentions from these conditions. This analysis specifically examined the age and sex distributions and places of death for each of these conditions, by whether they were coded as underlying or contributory causes of death. Major differences were found in age distribution, gender balance and place of death across these conditions, and there was also marked variations across these factors according to whether the conditions were recorded as underlying or contributory. The analysis then went on to examine patterns and effects of contributory codings of Alzheimer's disease, dementia and senility for major underlying cause of death groupings (circulatory diseases, malignant cancers, respiratory diseases) and found large differences across these groups. Place of death of each of these major groups was also examined according to whether contributory codings of Alzheimer's disease, dementia or senility were present and radical differences observed between populations with and without contributory codings. As the number of people with Alzheimer's disease, dementia and senility is projected to increase by over 70% in England between 2010 and 2030, these conditions are set to become increasingly important, both in terms of numbers of persons affected and resources consumed. Greater insight into the patterns and trends of these conditions is therefore essential to plan the provision of appropriate levels and patterns of care.